SARS-CoV: Lessons learned; opportunities missed for SARS-CoV-2 - Davis, Ian M. (2020)
SARS-CoV-2 and Covid-19 have made a retrospective analysis of other coronavirus diseases important, so this article reviews the history of the SARS-CoV viral disease from 2003. Standard and clinical chemistry diagnostics were developed in response to the outbreak. The response to SARS is examined to determine if there were lessons learned before it disappeared in June and July 2003. Various diagnostic approaches were developed and implemented to assist in the rapid identification of patients and treatment of their illness, yet many of the approaches required days or weeks from the onset of fever to show statistical significance. Most of the therapeutic methods used during the outbreak relied on treating symptoms of the underlying illness, such as lower respiratory infections and systemic infection, rather than effectively suppressing or curtailing replication of the virus. Retrospective studies are examined to determine how the SARS outbreak was viewed 10 years on and what the authors hoped would be instructive patterns for possible future pandemics. Implementation of some of these recommendations might have helped ease the current pandemic but were overlooked for budgetary reasons that seem short-sighted at present.